Prinsip Pengenalan Morfem dalam Bahasa Inggris: Kajian Morfologi - Suhila Mahamu; Agus Nero Sofyan (SUAR BETANG, 2021)
This research aims to classify and identify morphemes recognition in English. The method used in this study is qualitative descriptive method. In providing data, the researcher uses listening and note-taking technique. The data used in this study were retrieved from the book Top Grammar: A Guide to Write English. While the theory used is the theory of the principle of morpheme recognition. The results of this discussion can be classified into six principles of morpheme recognition namely (1) the form of indefinite pronouns, comparative and superlative degree and reflexive pronouns; (2) singular and plural forms; (3) the form of the past participle in regular {-d}/{-ed} and irregular {–n} forms; (4) singular and plural nouns, present and past verbs; (5) the form of homonyms and in principle; and (6), the form of free morpheme and bound morpheme. From the results of the classification, morpheme units can be identified based on word form, word class and also the meaning that appears.AbstrakPenelitian ini bertujuan untuk mengklasifikasi dan mengidentifikasi pengenalan morfem dalam bahasa Inggris. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Dalam tahapan penyediaan data, penulis menggunakan teknik simak dan catat. Data yang digunakan dalam penelitian ini bersumber dari buku Top Grammar: A Guide to Write English. Teori yang digunakan adalah teori prinsip pengenalan morfem. Hasil dari pembahasan menunjukan bahwa terdapat enam prinsip pengenalan morfem, yaitu (1) terdapat pada bentuk indefinite pronoun, comparative dan superlative degree, serta reflexive pronoun; (2) terdapat pada bentuk tunggal dan jamak; (3) terdapat data pada bentuk past participle bentuk regular {-d}/ {-ed} dan irregular {–n}; (4) terdapat padakata benda tunggal dan jamak dan kata kerja present serta past; (5) terdapat pada bentuk homonim; (6) terdapat pada bentuk morfem bebas dan terikat. Dari hasil klasifikasi tersebut dapat disimpulkan bahwa satuan morfem dapat diidentifikasi berdasarkan bentuk kata, kelas kata, dan makna yang muncul.